The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0241015
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to interaural time differences and localization accuracy in cochlear implant users with combined electric-acoustic stimulation

Abstract: In this study, localization accuracy and sensitivity to acoustic interaural time differences (ITDs) in subjects using cochlear implants with combined electric-acoustic stimulation (EAS) were assessed and compared with the results of a normal hearing control group. Methods Eight CI users with EAS (2 bilaterally implanted, 6 unilaterally implanted) and symmetric binaural acoustic hearing and 24 normal hearing subjects participated in the study. The first experiment determined mean localization error (MLE) for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
0
12
2
Order By: Relevance
“…We hypothesize that hearing asymmetries introduce localization biases to the better hearing ear ( Figure 1b to d). This would suggest that idiosyncratic localization abilities as demonstrated in earlier studies ( Dunn et al, 2010 ; Gifford Grantham et al, 2014 ; Dorman et al, 2016 ; Körtje et al, 2020 ) with errors ranging from near-normal (10 deg) to extremely poor (70 deg) may well depend on individual hearing asymmetries. Indeed, more symmetric hearing in bimodal EAS users correlates with the ability to process ITDs ( Gifford Grantham et al, 2014 ) and localize sounds ( Loiselle et al, 2015 ).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…We hypothesize that hearing asymmetries introduce localization biases to the better hearing ear ( Figure 1b to d). This would suggest that idiosyncratic localization abilities as demonstrated in earlier studies ( Dunn et al, 2010 ; Gifford Grantham et al, 2014 ; Dorman et al, 2016 ; Körtje et al, 2020 ) with errors ranging from near-normal (10 deg) to extremely poor (70 deg) may well depend on individual hearing asymmetries. Indeed, more symmetric hearing in bimodal EAS users correlates with the ability to process ITDs ( Gifford Grantham et al, 2014 ) and localize sounds ( Loiselle et al, 2015 ).…”
Section: Introductionmentioning
confidence: 78%
“…Criteria for cochlear implantation have been expanded to allow adults with good low-frequency hearing thresholds and severe-to-profound high-frequency hearing loss in both ears to receive a single cochlear implant. The combined electric and acoustic stimulation (EAS) in the implanted ear and acoustic stimulation in the other provides these cochlear implant recipients with binaural low-frequency acoustic hearing, which has been shown to improve horizontal-plane sound localization ( Dunn et al, 2010 ; Gifford et al., 2014 ; Plant & Babic; 2016; Kortje et al, 2020 ). However, these EAS listeners effectively have monaural (electrical) hearing for high frequencies and asymmetric (bimodal) hearing for mid frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preservation of the sensitivity to the binaural gap even when an interaural delay was introduced indicated that acoustic temporal fine structure features of noise were maintained for the duration of the interaural interval [11,25,26] and allowed similarity computation between the binaural sound inputs. Thus, measuring the impact of interaural delay when the binaural gap is detected [27][28][29] can provide a way of investigating the transient memory of acoustic features.…”
Section: Introductionmentioning
confidence: 99%